PENERAPAN MEDIA KARTU HURUF DALAM PEMBELAJARAN DI TK NEGERI PEMBINA SUBAH - Lestari Lestari; Eliyah Eliyah (CV. ADIBA AISHA AMIRA, 2023)
This study aims to find out how the teacher's creativity in making learning media, especially letter card media, how the media used can improve student competence. The method used is action research method. By actualizing the design that is designed into learning. The results of the study showed: The innovations carried out in this activity in the form of applying letter card media have succeeded in increasing the Language Development of KD 3.12 children to recognize early literacy through playing on indicators of recognizing letter sounds. In carrying out this activity it can be seen that 10 children have entered the Developing According to Expectations (BSH) stage. This proves that there is an increase in children's language development using letter card media, because previously only 5 children reached the Developing According to Expectations (BSH) stage.